Phylogenetic distribution of symbiotic bacteria from Panamanian amphibians that inhibit growth of the lethal fungal pathogen Batrachochytrium dendrobatidis. Issue 7 (April 2015) - Becker, Matthew H.; Walke, Jenifer B.; Murrill, Lindsey; Woodhams, Douglas C.; Reinert, Laura K.; Rollins‐Smith, Louise A.; Burzynski, Elizabeth A.; Umile, Thomas P.; Minbiole, Kevin P. C.; Belden, Lisa K.
Abstract: The introduction of next‐generation sequencing has allowed for greater understanding of community composition of symbiotic microbial communities. However, determining the function of individual members of these microbial communities still largely relies on culture‐based methods. Here, we present results on the phylogenetic distribution of a defensive functional trait of cultured symbiotic bacteria associated with amphibians. Amphibians are host to a diverse community of cutaneous bacteria and some of these bacteria protect their host from the lethal fungal pathogen Batrachochytrium dendrobatidis (Bd) by secreting antifungal metabolites. We cultured over 450 bacterial isolates from the skins of Panamanian amphibian species and tested their interactions with Bd using an in vitro challenge assay. For a subset of isolates, we also completed coculture experiments and found that culturing isolates with Bd had no effect on inhibitory properties of the bacteria, but it significantly decreased metabolite secretion. In challenge assays, approximately 75% of the bacterial isolates inhibited Bd to some extent and these inhibitory isolates were widely distributed among all bacterial phyla. Although there was no clear phylogenetic signal of inhibition, three genera, Stenotrophomonas, Aeromonas and Pseudomonas, had a high proportion of inhibitory isolates (100%, 77% and 73%, respectively). Overall, our results demonstrate that antifungal properties are phylogenetically widespread in symbiotic microbial communities of Panamanian amphibians and that some functional redundancy for fungal inhibition occurs in these communities. We hope that these findings contribute to the discovery and development of probiotics for amphibians that can mitigate the threat of chytridiomycosis.